ZOO Brno - Tropické království - Kozlová, Natálie (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Pavilon Tropického království v ZOO Brno je umístěn v jižní části areálu na svažitém terénu, obklopený bohatou zelení. Moderní stavba s vegetační střechou a skleněným zastřešením harmonicky zapadá do krajiny. Pavilon je navržen s ohledem na bezpečnost, udržitelnost a komfort zvířat i návštěvníků, včetně bezbariérového přístupu. Komplex zahrnuje tři části: hlavní pavilon krokodýlí jeskyně s podvodním pohledem na krokodýly, tropický deštný les s výběhy pro ptáky a Mlžný les pro opičky a noční savce. Spojovací prostory obsahují akvária pro sladkovodní i mořské živočichy. Exteriér i interiér využívají kombinaci šetrných materiálů, šedých tónů, zeleně a průhledného skla, které posilují tropickou atmosféru.

The Pavilion of the Tropical Kingdom in ZOO Brno is located in the southern part of the area on a sloping terrain, surrounded by rich greenery. The modern building with a vegetated roof and glass roof fits harmoniously into the landscape. The pavilion is designed with the safety, sustainability and comfort of animals and visitors in mind, including barrier-free access. The complex includes three parts: the main crocodile cave pavilion with an underwater view of crocodiles, a tropical rainforest with enclosures for birds and a Misty Forest for monkeys and nocturnal mammals. Connecting areas contain aquariums for freshwater and marine animals. The exterior and interior use a combination of gentle materials, gray tones, greenery and transparent glass, which reinforce the tropical atmosphere.
ZOO Brno - Tropical Kingdom
Keywords: ZOO; zoologická zahrada; pavilon krokodýlů; tropický les; mlžný les; primáti; noční savci; pavilion Tropické království; pavilon; akvárium; mořské akvária; hmyz; terárium; Zoo; zoo; crocodile pavilion; tropical forest; cloud forest; primates; nocturnal mammals; Tropical Kingdom pavilion; pavilion; aquarium; marine aquariums; insects; terrarium